Measuring air quality using Arduino via APC220 radio data module - Haris, Muhamad Harnika Rifhan (2014)
The thesis is to present and design a device that could monitor air quality in a certain place even in indoor or outdoor for human healthcare. This device could detect a Particulate Matter 2.5 (PM2.5) for an air quality in the area. This paper presents the system development by using Matlab for graphical indicator, and using Arduino UNO as an input/output data to detect dust and gas quality. Using the Arduino device, it uses Optical Sharp Dust Sensor to measure air quality for existence of a dust. Also using an analog gas sensor (QM-NG1) for detecting hydrogen that could give out an alarm for a gas leak. And its uses LM35 to measure a temperature at a measured place. For this prototype, this paper proposes using APC220 as a connection between prototype and serial main monitor on a computer by using RF wireless radio connection. All the value has been mentioned will be interpreted in MATLAB. This research project is useful for air quality for department of environment.